Earnings Quality and Its Determinants: An Analysis of Profitability, Liquidity, and Investment Opportunity Set - Ghaisani, Citra Awanis (E-Jurnal Akuntansi; Vol 35 No 4 (2025), 2025)
The objective of this study is to investigate the impact of profitability, liquidity, and the investment opportunity set on earnings quality. This study focuses on manufacturing firms that were listed between 2018 and 2022 on the Indonesia Stock Exchange using a quantitative approach. The sampling technique observing 165 manufacturing company with total samples are 856 data. The findings of the investigation suggest that, although the investment opportunity set exerts a positive influence, profitability and the liquidity variable have a negative impact. This research underscores the critical need for accurate financial reporting, especially considering past financial scandals that have affected investor trust and makes a substantial contribution to the comprehension of the elements affecting the earning quality in manufacturing firms on Indonesia. Keywords: Profitability; Earning Quality; Investment Opportunity Set; Liquidity.